ISO 9001 certification and the quality management system of EPS SEDA-Huanuco - Calero, Roberto (2022)
Objective. To analyze the influence of the implementation of the ISO 9001:2015 Standard on the quality management system of the sanitation services provider company of the Huanuco region (EPS SEDA-Huanuco) for the year 2018. Methods. Due to its purpose, the research was characterized as basic. It had a descriptive-correlational level and adopted a non-experimental design. The data were obtained in two ways: (i) application of a survey questionnaire addressed to the operational and administrative personnel and senior management of the EPS; (ii) the database on user satisfaction applied by the EPS itself. On this basis, correlations between the variables were estimated. Results. Evidence was found indicating that the implementation of ISO 9001 has a positive relationship with user satisfaction (rho=0.81), service quality assurance (rho=0.78) and overall EPS improvement (rho=0.82) during 2018. Conclusions. It is established that the implementation of ISO 9001 certification has a positive influence on user satisfaction, service quality assurance and the overall improvement of EPS SEDA-Huánuco.